Tufted NiCo2O4 Nanoneedles Grown on Carbon Nanofibers with advanced electrochemical property for Lithium Ion Batteries. (20th December 2016) - Zhou, Gang; Wu, Chen; Wei, Yuehua; Li, Chengchao; Lian, Qingwang; Cui, Chao; Wei, Weifeng; Chen, Libao
Graphical abstract: Highlights: Tufted NiCo2 O4 nanoneedles grown on carbon nanofibers (TNN/CNFs) were successfully fabricated by facile hydrothermal and annealing procedure. The composite possesses a unique three-dimensional (3D) hybrid structure and morphology. The composite delivers a reversible discharge specific capacity up to 1033.6 mAh g −1 even after 250 cycles. The outstanding electrochemical performance origins from unique 3D hybrid structure. Abstract: In this article, tufted NiCo2 O4 nanoneedles directly grown on carbon nanofibers (CNFs) were successfully fabricated by a facile hydrothermal procedure and subsequent annealing. The morphology of tufted NiCo2 O4 nanoneedles/carbon nanofibers (TNN/CNFs) composite appears like clustered acicular leaves on branches, forming a unique three dimensional (3D) hybrid structure. Compared to NiCo2 O4 nanoneedles spheres (NNS) without CNFs, the TNN/CNFs material presents a reversible discharge specific capacity up to 1033.6 mAh g −1 at a current density of 200 mA g −1 even after 250 cycles, with the coulombic efficiency of above 98%. The unique 3D hybrid structure formed with CNFs should be responsible for the superior lithium storage capacity and enhanced cycling performance, which provides short distance for ions transport, high specific surface area for large contact areas between electrode and electrolyte, together with the interspace to accommodate volume change and smaller agglomeration tendency. Moreover, the design route proposed offers more possibility to preparation of high-performance anode materials for LIBs.